2013
DOI: 10.1126/scitranslmed.3005265
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Interleukin-2 Therapy Restores Regulatory T Cell Homeostasis in Patients with Chronic Graft-Versus-Host Disease

Abstract: CD4+FoxP3+ regulatory T cells (Tregs) play a central role in the maintenance of immune tolerance after allogeneic hematopoietic stem cell transplantation. We recently reported that daily administration of low-dose IL-2 induces selective expansion of functional Treg and clinical improvement of chronic graft-versus-host disease (GVHD). To define the mechanisms of action of IL-2 therapy we examined the immunologic effects of this treatment on homeostasis of CD4 T cell subsets after transplant. We first demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
343
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 411 publications
(387 citation statements)
references
References 48 publications
16
343
0
5
Order By: Relevance
“…Treg homeostasis is altered in cGVHD and adoptive transfer or in vivo induction of Tregs may prevent or improve the symptoms of cGVHD. [2][3][4][5] Our understanding of the function of Bregs in this disease is limited. IL-10-producing B cells have been shown to inhibit CD4 T-cell proliferation, 6 TNF-a and IFN-g production, 21 and monocyte activation 7 in in vitro coculture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Treg homeostasis is altered in cGVHD and adoptive transfer or in vivo induction of Tregs may prevent or improve the symptoms of cGVHD. [2][3][4][5] Our understanding of the function of Bregs in this disease is limited. IL-10-producing B cells have been shown to inhibit CD4 T-cell proliferation, 6 TNF-a and IFN-g production, 21 and monocyte activation 7 in in vitro coculture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observed proliferative effect of in vivo low dose IL-2 on Tregs. 27 The IL2DT cohort demonstrated that lack of host Tregs is associated with improved in vivo donor NK-cell expansion and remission induction. However, in addition to IL2DT, cohort 3 also received products with higher NK cells doses, which may have contributed to the better clinical results.…”
Section: Foxp3mentioning
confidence: 99%
“…To restore Treg homeostasis at chronic phase (that is, "maintenance phase" in Fig. 3), a phase 1 dose-escalation study aimed at exploring the maximum tolerated dose of daily low-dose subcutaneous IL-2 in patients with steroid-refractory chronic GVHD was conducted at Dana-Farber Cancer Institute [18,19]. Twenty-nine patients were included, and the maximum tolerated dose of IL-2 was 1 × 10 6 IU/m 2 .…”
Section: Therapeutic Intervention In Treg Homeostasis By Low-dose Il-2mentioning
confidence: 99%
“…12 of 23 evaluable patients achieved an objective partial response during the 8 weeks of IL-2 treatment. IL-2 therapy induced a series of changes in Treg homeostasis, including increased proliferation, increased thymic export, and enhanced resistance to apoptosis [19]. Based on these promising results, a Phase 2 study with low-dose (1 × 10 6 IU/m 2 /day) IL-2 was conducted and elucidated that clinical responders initiated IL-2 significantly earlier (508 versus 917 days after HSCT) and Treg:Tcon ratios ≥ 0.07 at baseline and ≥ 0.2 at week 1 also predicted clinical response [31,32].…”
Section: Therapeutic Intervention In Treg Homeostasis By Low-dose Il-2mentioning
confidence: 99%
See 1 more Smart Citation